2016
DOI: 10.1111/pan.12855
|View full text |Cite
|
Sign up to set email alerts
|

Rectus sheath and transversus abdominis plane blocks in children: a systematic review and meta‐analysis of randomized trials

Abstract: Abdominal wall blocks reduce pain and opiate use in children. We advise cautious interpretation of the results given the heterogeneity of studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
24
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(28 citation statements)
references
References 43 publications
1
24
0
3
Order By: Relevance
“…This may be explained by the high quality of analgesia and the lower use of opioids. However, in previous reports concerning children, such a correlation was not observed -a lower requirement for opioids in the TAP block group did not correspond with a decreased incidence of postoperative [3,7,14,15].…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…This may be explained by the high quality of analgesia and the lower use of opioids. However, in previous reports concerning children, such a correlation was not observed -a lower requirement for opioids in the TAP block group did not correspond with a decreased incidence of postoperative [3,7,14,15].…”
Section: Discussionmentioning
confidence: 55%
“…There have been reports that larger volume of the local anaesthetic (1-2 mL kg -1 ) may spread to the paravertebral space and extend a range of analgesia, providing partial exclusion of the painful stimuli from the viscera [9]. Previous research results mainly show that the TAP block decreases pain perception, reduces the requirement for analgesics in the postoperative period and increases time span from the end of the anaesthesia to the first dose of analgesics in children after abdominal surgery [3,10,11]. However, there are also individual reports which do not confirm this data [12,13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…68 ERAS interventions include pre-operative education, optimizing analgesia, avoidance of drains or nasogastric tubes, early post-operative feeding and early mobilization. Local 69 and regional 70 anaesthesia has shown benefit in laparoscopic appendicectomy, but evidence does not support a preference of administration of local anaesthetic prior to skin incision (pre-emptive analgesia) versus at the end of laparoscopy. 71 Patient-controlled analgesia appears beneficial in perforated appendicitis 72 but increases opiate use and pruritis, 73 which could delay discharge after uncomplicated appendicitis.…”
Section: Modern Recoverymentioning
confidence: 99%
“…Four prospective non-randomized studies [74][75][76][77] and three retrospective studies [78][79][80] have shown same day discharge or 'outpatient' appendectomy to be feasible and safe in contrast to the 3-week convalescence of patients at the turn of the previous century. In addition to optimal access, interventions to improve recovery include local anaesthetic at port sites, 69 regional blocks, 70 optimizing systemic analgesics 72 and rationalizing post-operative antibiotics. 81 …”
Section: Modern Recoverymentioning
confidence: 99%